Margföldun – Æfing 3.3 – Lausnir

  1. (x + 2)(x – 4) = x2 + 2x – 4x – 8 = x2– 2x – 8
  2. (x + 1)x – (x – 2)(x + 1) = x2 + x – (x2 – 2x + x – 2) = x2 + x – (x2– x – 2) = x2 + x – x2 + x + 2 = 2x + 2
  3. 5(x + 7) – 3(2x – 1) = 5x + 35 – 6x + 3 = -x + 38
  4. (x + 1)(x – 6) = x2 – 6x + x – 6 = x2 – 5x – 6
  5. x(2x + 3) + 2(x – 1) = 2x2 + 6x + 2x – 2 = 2x2 + 8x – 2
  6. (r + s + 1)(r + 1) = r2 + r + rs + s + r + 1 = r2 + 2r + rs + s + 1
  7. 8(v + s + x) – 2(3v – 4s + 2x) = 8v + 8s + 8x – 6v + 8s – 4x = 2v + 16s + 4x